A clinician's dilemma: what should be communicated to women with oncogenic genital HPV and their partners regarding the risk of oral viral transmission? - Ermelinda Monti; Giussy Barbara; Giada Libutti; Veronica Boero; Fabio Parazzini; Andrea Ciavattini; Giorgio Bogani; Lorenzo Pignataro; Beatrice Magni; Camilla Erminia Maria Merli; Paolo Vercellini (BMC, 2022)
Abstract Head and neck cancer, the sixth most common cancer worldwide, account for about 1 out of 20 malignant tumors. In recent years a reduction in the incidence of cervical cancer, but a concomitant major increase in the incidence of HPV-mediated oropharyngeal cancer caused by orogenital HPV transmission has been observed. Consequently, in wealthy countries oropharyngeal squamous-cell carcinomas (OPSCC) is now the most frequent HPV-related cancer, having overtaken cervical cancer. Without effective medical interventions, this incidence trend could continue for decades. As no specific precursor lesion has been consistently identified in the oral cavity and oropharynx, HPV vaccination is the logical intervention to successfully counteract also the rising incidence of OPSCCs. However, HPV vaccine uptake remains suboptimal, particularly in males, the population at higher risk of OPSCC. Alternative primary prevention measures, such as modifications in sexual behaviors, could be implemented based on knowledge of individual genital HPV status. Until recently, this information was not available at a population level, but the current gradual shift from cytology (Pap test) to primary HPV testing for cervical cancer screening is revealing the presence of oncogenic viral genotypes in millions of women. In the past, health authorities and professional organizations have not consistently recommended modifications in sexual behaviors to be adopted when a persistent high-risk HPV cervicovaginal infection was identified. However, given the above changing epidemiologic scenario and the recent availability of an immense amount of novel information on genital HPV infection, it is unclear whether patient counseling should change. The right of future partners to be informed of the risk could also be considered. However, any modification of the provided counseling should be based also on the actual likelihood of a beneficial effect on the incidence of HPV-associated oropharyngeal cancers. The risk is on one side to induce unjustified anxiety and provide ineffective instructions, on the other side to miss the opportunity to limit the spread of oral HPV infections. Thus, major health authorities and international gynecologic scientific societies should issue or update specific recommendations, also with the aim of preventing inconsistent health care professionals' behaviors.